HUBUNGAN KETERPAPARAN INFORMASI, DUKUNGAN KELUARGA DAN PETUGAS KESEHATAN TERHADAP PENERIMAAN VAKSIN COVID-19 PADA LANSIA RW 007 KELURAHAN BIDARA CINA TAHUN 2021 - Elma Manzila Putri (2021)
The elderly are an age group that has a high risk of being infected with COVID-19 because at this age there is a decrease in body functions. The high mortality rate of COVID-19 in the elderly is 48.5% causing the need for vaccines as a form of protection for the elderly. However, until now the coverage of COVID-19 vaccine acceptance in the elderly is still low. Factors that affect the acceptance of the COVID-19 vaccine are individual, environmental, and social processes. This study aims to analyze the relationship between information exposure, family support, and health care workers' support for the acceptance of the COVID-19 vaccine. This research is using quantitative method with cross sectional research design and the statistical test was the Chi Square test with 0,05 significance. The research was conducted from April-June 2021 at RW 007 Kelurahan Bidara Cina with a sample of 226 people. The sampling technique was purposive sampling. Based on the results showed that 51.3% did not receive the vaccine. The result of bivariate analysis showed that there was a significant relationship between information exposure (p-value=0,000), family support (p-value=0,000), and health workers support (p-value=0,000) with COVID-19 vaccine acceptance. The elderly are advised to participate in receiving the COVID-19 vaccine.